Jean Bodin: dalla tolleranza alla libertà religiosa (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Premessa - 2. Dalla tolleranza alla possibilità di “riconoscere nel cuore un Dio incorporeo e altissimo” - 3. La libertà religiosa aconfessionale nella definizione della sovranità assoluta - 4. La potestà aconfessionale della sovranità statale e il separatismo - 5. Dalla ragion di Stato della “suprema potestà statale” alla libertà religiosa nell’esercizio della giurisdizione - 6. Conclusione.Jean Bodin from Tolerance to Religious FreedomABSTRACT: Absolutism, in France, rises also in order to resolve religious conflicts, affirming the national community and the interests of the State. This is an evaluation that leads to thinking, above all, about J. Bodin and Les le livres de la Republique and to “read” the relationship between "tolerance" and "religious liberty". Bodin indicates the limits of religious tolerance - that is based on the dogma of the exclusive confessional salvation - that reveals to religious freedom in the theorization of the absolute State. The freedom to manifest own religious conviction does not undergo to any presumption of exclusive salvation because it intends to proclaim publicly, but also privately, what the individual perceives in consciousness. A dimension of secularism really particular, that reveals the difficult political condition of the wars of religion. The coexistence of the only God, which divine laws sanction in the definition of sovereignty, suggests an overcoming of the confessionism. The civil legal significance of religious confessions lives the confessional dimension of interreligious dialogue for an understanding of the "incorporeal and supreme" God of the "Colloquium Heptaplomeres".